2019
DOI: 10.1016/j.jor.2019.03.024
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in obesity prevalence among total hip arthroplasty patients and the effect on surgical outcomes, 2008–2016

Abstract: Introduction:The prevalence of obesity continues to rise in parallel with demand for total hip arthroplasty (THA). This study aims to report obesity trends in primary THA and its effects on procedure outcomes in the United States, stratifying based on Body Mass Index (BMI). Methods: Primary THA procedures were identified in the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Patient demographic (including BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…While a body mass index (BMI) exceeding 30 kg/m 2 is not a true reflection of general state of health or fitness level, the medical co-morbidities of obesity (BMI!30 kg/m 2 ) are well documented, and there is an association with the development of hip osteoarthritis 2,3 . The increase in BMI across our population has implications for both the numbers of hip and knee arthroplasties being performed but also for subsequent outcomes 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…While a body mass index (BMI) exceeding 30 kg/m 2 is not a true reflection of general state of health or fitness level, the medical co-morbidities of obesity (BMI!30 kg/m 2 ) are well documented, and there is an association with the development of hip osteoarthritis 2,3 . The increase in BMI across our population has implications for both the numbers of hip and knee arthroplasties being performed but also for subsequent outcomes 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a rising rate of obesity in the United States. In an investigation of the American College of Surgeons National Surgical Quality Improvement Program database, Pirruccio et al [4] identified an increase in the prevalence of obesity in total hip arthroplasties (THAs) from 45.5% in 2008 to 47.1% in 2016. Correspondingly, we can continue to expect more patients presenting with musculoskeletal consequences from obesity including osteoarthritis and debilitating joint pain.…”
mentioning
confidence: 99%
“…The prevalence of obesity continues to rise in parallel with the demand for total hip arthroplasty (Pirruccio et al, 2019). A relationship between surgical site infection (SSI) and morbid obesity or diabetes has consistently been reported; although both conditions are often concurrent, both diabetes and morbid obesity independently contribute to SSI risk.…”
Section: Discussionmentioning
confidence: 99%